Wage discrimination over the business cycle - Jeff E. Biddle; Daniel S. Hamermesh (IZA Journal of Labor Policy, 2013)
Using CPS data from 1979-2009 we examine how cyclical downturns and industry-specific demand shocks affect wage differentials between white non-Hispanic men and women, Hispanics and non-Hispanic whites, and African-Americans and non-Hispanic whites. Women's relative earnings are harmed by negative shocks; the wage disadvantage of African-Americans drops with negative shocks, while the impact on Hispanics' wages is unclear. A theory of job search suggests two opposite-signed mechanisms that affect these wage differentials. It suggests greater absolute effects among job-movers, which is verified using the longitudinal component of the CPS.
Keywords: J7; E3; 330; wage discrimination; business cycles